2014
DOI: 10.1016/j.ydbio.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel retinoic acid target genes

Abstract: Retinoic acid is required for diverse ontogenic processes and as such identification of the genes and pathways affected by retinoic acid is critical to understanding these pleiotropic effects. The presomitic mesoderm of the E8.5 mouse embryo is composed of undifferentiated cells that are depleted of retinoic acid, yet are competent to respond to the retinoid signal. We have exploited these properties to use this tissue to identify novel retinoic acid-responsive genes, including candidate target genes, by treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…We have previously characterized the solution structures of the RXRA ΔAB-RARA ΔAB and RXRΔAB–RARA ΔABF complexes with the Rarb2 DR5 ( 60 ) and have shown that the presence of the RARA F domain leads to an increase in structural parameters indicating an extended non-interacting F domain. We now have selected another DR5 element from the F11r gene ( Supplementary Figure S1 ) which has been identified as a regulated RARE ( 13 , 61 ) and which exhibits similar binding as the Rarb2 DR5 ( 56 ) and Hoxb13 DR0 for which the polarity is defined as unique. The use of the coupled SEC-SAXS-TDA and the measurement of their subsequent SAXS intensity profiles (measured as I ( s ) versus s , where s = 4πsin θ /λ, 2 θ is the scattering angle) and the validation of the corresponding molecular weights (MWs) from the TDA that were compared to the MWs obtained directly from the SAXS data ( Supplementary Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously characterized the solution structures of the RXRA ΔAB-RARA ΔAB and RXRΔAB–RARA ΔABF complexes with the Rarb2 DR5 ( 60 ) and have shown that the presence of the RARA F domain leads to an increase in structural parameters indicating an extended non-interacting F domain. We now have selected another DR5 element from the F11r gene ( Supplementary Figure S1 ) which has been identified as a regulated RARE ( 13 , 61 ) and which exhibits similar binding as the Rarb2 DR5 ( 56 ) and Hoxb13 DR0 for which the polarity is defined as unique. The use of the coupled SEC-SAXS-TDA and the measurement of their subsequent SAXS intensity profiles (measured as I ( s ) versus s , where s = 4πsin θ /λ, 2 θ is the scattering angle) and the validation of the corresponding molecular weights (MWs) from the TDA that were compared to the MWs obtained directly from the SAXS data ( Supplementary Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…34 In our data we found that the Ccnb1 mRNA was downregulated from the pre-leptotene stage, which suggests that Ccnb1 is dispensable for the meiocytes' chromatin remodeling. In addition, the Ccnd1 targeted by RA is highly expressed in the pre-leptotene cluster, 25 which suggests that it may be involved in the regulation of meiosis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by a recent study using embryonal day 8.5 mouse embryos. When treated with RA, SALL4 was identified as one of the most severely down-regulated genes in the presomitic mesoderm (28). In our ChIP assays, ATRA treatment also led to decreased SALL4 binding to target genes and dissociation of SALL4 and epigenetic corepressors from RAR␣ (Fig.…”
Section: Discussionmentioning
confidence: 60%